Validation of the Sentinel-3 SLSTR LST product using in-situ data from meteorological stations in Cyprus - Loulli, Eleni; Hadjimitsis, Diofantos G. (My University, 2019)
Cyprus has Mediterranean and semi-arid climate. Such climates are characterized by mild and rainy winters, and dry summers with less than 40 mm of precipitation for at least three summer months. Drought is a natural phenomenon that appears frequently in Cyprus and has several impacts in water supply. Drought assessment and monitoring are thus, vital in mitigating drought impacts and managing water resources efficiently. Land Surface Temperature (LST) is an essential parameter in drought monitoring. It provides significant insights to assess vegetation health and soil moisture level. The extreme heterogeneity of most natural land surfaces makes the estimation and validation of LST a demanding procedure. The Sea and Land Surface Temperature Radiometer (SLSTR) on the ESA/EU GMES Sentinel-3 mission provides highly accurate measurements of global Earth surface temperatures. Its SLSTR Level-2 LST product offers land surface parameters generated on the wide 1 km measurement grid. In this work, we present the validation results of the Sentinel-3 Level-2 LST using in-situ meteorological data obtained from the year 2017 onwards. The in-situ data were provided from the Meteorological Service of Cyprus. The validation includes data from existing meteorological stations located at different locations to understand the influence of the prevailed vegetation and land surface heterogeneity on satellite observations better. Future work will involve the estimation and validation of LST using Landsat satellite data acquired from the year 2000 onwards. This will ensure the LST data continuity for a period that is longer than 10 years, a requirement that is evident in drought assessment and monitoring.
Keywords: drought monitoring; land surface temperature; validation; Sentinel-3 SLSTR; meteorological data